2020
DOI: 10.1158/1535-7163.mct-20-0410
|View full text |Cite
|
Sign up to set email alerts
|

Anti-S100A4 Antibody Therapy Is Efficient in Treating Aggressive Prostate Cancer and Reversing Immunosuppression: Serum and BiopsyS100A4as a Clinical Predictor

Abstract: ◥S100A4 oncoprotein plays a critical role during prostate cancer progression and induces immunosuppression in host tissues. We hypothesized that S100A4-regulated oncogenic activity in immunosuppressed prostate tumors promotes growth of neoplastic cells, which are likely to become aggressive. In the current study, we investigated whether biopsy-S100A4 gene alteration independently predicts the outcome of disease in patients and circulatory-S100A4 is druggable target for treating immunosuppressive prostate cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Then, we identified a total of 23 ARGs that significantly correlated with PCa patients' survival. In concordance with previous studies which investigate the ARG solely in prostate cancer, genes including NRP1 (Tse et al 2017), JAG2 (Kwon et al 2016), COL5A2 (Ren et al 2021), POSTN (Cattrini et al 2018), FSTL1 (Zhao et al 2019), PF4 (Baselga et al 2008), JAG1 (Terada et al 2014), COL3A1 (Angel et al 2020), VCAN (Asano et al 2017), VEGFA (Zhan et al 2013), SPP1 (Pang et al 2019), VTN (Niu et al 2016), and S100A4 (Ganaie et al 2020) were identified as unfavorable prognosis-related biomarkers in prostate cancer. Meanwhile, the prognosis roles of APP (Takayama et al 2009) and FGFR1 (Yang et al 2013b) were controversial with previous studies, which needed further validation and study.…”
Section: Discussionsupporting
confidence: 88%
“…Then, we identified a total of 23 ARGs that significantly correlated with PCa patients' survival. In concordance with previous studies which investigate the ARG solely in prostate cancer, genes including NRP1 (Tse et al 2017), JAG2 (Kwon et al 2016), COL5A2 (Ren et al 2021), POSTN (Cattrini et al 2018), FSTL1 (Zhao et al 2019), PF4 (Baselga et al 2008), JAG1 (Terada et al 2014), COL3A1 (Angel et al 2020), VCAN (Asano et al 2017), VEGFA (Zhan et al 2013), SPP1 (Pang et al 2019), VTN (Niu et al 2016), and S100A4 (Ganaie et al 2020) were identified as unfavorable prognosis-related biomarkers in prostate cancer. Meanwhile, the prognosis roles of APP (Takayama et al 2009) and FGFR1 (Yang et al 2013b) were controversial with previous studies, which needed further validation and study.…”
Section: Discussionsupporting
confidence: 88%
“…In PC, the role of S100A4-antibody therapy and its clinical applicability in treating immunosuppressive PC patients has previously been suggested [25]. Its role in promot- Although all markers are statistically significant (see Table 1) S100A4 is the biomarker with the best performance, with an AUC value of 0.735 (95% CI = 0.668-0.803) and a specificity of 90.32%.…”
Section: Discussionmentioning
confidence: 96%
“…Fluids biomarkers currently in use for diagnosis, prognosis, and relapse-monitoring of localized PC remain centered around PSA, with new strategies for genomic biomarkers still presenting a challenge [24]. At present, the established prognostic factors (ISUP, stage, and PSA) are insufficient to separate PC patients with high risk of cancer progression; moreover, molecular markers for metastatic propensity remain elusive [25]. RNA biomarkers are experiencing an increased interest in predicting progression-free survival and OS [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, S100A4 is considered a metastasis-promoting factor also because the protein Moreover, S100A4 is considered a metastasis-promoting factor also because the protein is released by activated stromal cells (e.g., fibroblasts, immune and vascular cells) in the tumor microenvironment, where it fosters growth factors release, angiogenesis and overall tumor survival. The increased protein secretion associated with tumor development and invasiveness has made S100A4 a good biomarker for different metastatic cancers, where it also assumes a prognostic value, since its increase is associated with poor patients survival [12][13][14][15][16]. Besides these roles, S100A4 controls different cellular pathways, exerting in this way numerous effects on processes that are cell-and tissue-type dependent.…”
Section: Introductionmentioning
confidence: 99%